Peripheral and central giant cell lesions: etiology, origin of giant cells, diagnosis and treatment - Rodrigo Gadelha Vasconcelos; Marcelo Gadelha Vasconcelos; Lélia Maria Guedes Queiroz (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION AND OBJECTIVE: The peripheral and central giant cell lesions (PGCL and CGCL) are a group of pathological entities with similar histopathological features and whose origin has not been fully elucidated. The former is reactive and the latter exhibits a non-neoplastic proliferative behavior. This article aims to review the literature on peripheral giant cell lesions (PGCL) and central giant cell lesions (CGCL) by discussing the most important aspects pertaining to each of them. RESULTS: These lesions are found in different locations and show diverse clinical signs despite having the same histopathological features. The treatment consists in the surgical resection by different techniques depending on the type of the lesion and clinical conditions. In the case of CGCL, drug therapy may also be employed. CONCLUSION: Although there is no consensus in the literature, it is essential to know the etiology of these lesions as well as the exact origin of the giant cells. Due to their singular biological behavior, it is of utmost importance to establish a differential diagnosis between the two lesions and other processes that have similar clinical, radiological and histological characteristics, inasmuch as this procedure is essential to provide a suitable treatment and establish a prognosis.